Recommendations on the Indications for RBC Transfusion for the Critically Ill Child Receiving Support From Extracorporeal Membrane Oxygenation, Ventricular Assist, and Renal Replacement Therapy Devices From the Pediatric Critical Care Transfusion and Anemia Expertise Initiative. (September 2018) - Bembea, Melania M.; Cheifetz, Ira M.; Fortenberry, James D.; Bunchman, Timothy E.; Valentine, Stacey L.; Bateman, Scot T.; Steiner, Marie E.
Abstract : Objectives: To present recommendations and supporting literature for RBC transfusions in critically ill children supported with extracorporeal membrane oxygenation, ventricular assist devices, or renal replacement therapy. Design: Consensus conference series of international, multidisciplinary experts in RBC transfusion management of critically ill children. Methods: The panel of 38 experts developed evidence-based, and when evidence was lacking, expert-based clinical recommendations as well as research priorities for RBC transfusions in critically ill children. The extracorporeal membrane oxygenation/ventricular assist device/renal replacement therapy subgroup included six experts. We conducted electronic searches of the PubMed, EMBASE, and Cochrane Library databases from 1980 to May 2017, using medical subject heading terms and text words to define concepts of RBC transfusion, extracorporeal membrane oxygenation, ventricular assist device, and renal replacement therapy. We used a standardized data extraction form to construct evidence tables and graded the evidence using the Grading of Recommendations Assessment, Development, and Evaluation system. Recommendations developed and supporting literature were reviewed and scored by all panel members. Agreement was obtained using the Research and Development/UCLA Appropriateness Method. Results: For inpatients requiring extracorporeal membrane oxygenation, ventricular assist device, or renal replacement therapy support, there was expert agreement (> 80%) on five good practice statements aimed to improve accuracy and uniform reporting of RBC transfusion data in pediatric extracorporeal membrane oxygenation, ventricular assist device, and renal replacement therapy studies and quality improvement projects; four clinical recommendations of physiologic metrics and biomarkers of oxygen delivery, in addition to hemoglobin concentration, to guide RBC transfusion, acknowledging insufficient evidence to recommend specific RBC transfusion strategies; and eight research recommendations. Conclusions: Further research surrounding indications, risks, benefits, and alternatives to RBC transfusion in children on extracorporeal devices is clearly needed. Using a structured literature review and grading process, the Transfusion and Anemia Expertise Initiative panel concluded that there is currently insufficient evidence to recommend specific RBC transfusion variables in children requiring extracorporeal membrane oxygenation, ventricular assist device, or renal replacement therapy support. Abstract : Supplemental Digital Content is available in the text.